P261 Clinical outcomes of high-frequency repetitive transcranial magnetic stimulation (HF-rTMS) and electroconvulsive therapy (ECT) in the treatment of major depression. An overview of findings from meta-analyses. Issue 3 (March 2017) - Kedzior, K.K.; Schuchinsky, M.; Müller, C.; Engelhardt, T.- C.; Kappen, C.; Loo, C.
Abstract : Background: Meta-analyses comparing the short-term clinical outcomes of high-frequency repetitive transcranial magnetic stimulation (HF-rTMS) and electroconvulsive therapy (ECT) in major depression produced conflicting results. The aim of the current study was to summarise the results of these meta-analyses. Methods: A systematic literature search of PubMed and PsycInfo (any time – 13.01.2016) identified k = 4 systematic reviews (published in 2010–2014) comparing the clinical outcomes of ECT and HF-rTMS in major depression using quantitative meta-analysis. The short-term outcomes were the standardised mean change scores (baseline – last stimulation) on depression scales and odds or risk ratios of response, remission, and acceptability (dropout) rates. Since different meta-analytical approaches were used, we have pooled the effects using random-effects model with inverse-variance weights based on data shown in reviews. Results: The k = 4 reviews included different combinations of k = 8 open-label or single-blind, randomised primary studies with major depression patients. Most studies utilised right unilateral ECT (2.5 times the seizure threshold, 6–12 sessions) and HF-rTMS (10–20 Hz) of the left dorsolateral prefrontal cortex (90–110% of the resting motor threshold, 10–20 sessions). The pooled weighted effects favoured ECT over HF-rTMS in terms of reduction in depression severity (change scores in k = 2 reviews), while response and acceptability rates of both methods were similar (in k = 2 and k = 3 reviews respectively), and remission rates were inconsistent in k = 3 reviews (possibly due to heterogeneous definitions of remission). The individual study effect sizes favoured ECT over HF-rTMS in terms of reduction in depression severity and remission rate in studies with psychotic major depression patients. Conclusion: Uniform meta-analytical approaches suggest that ECT might be clinically superior to HF-rTMS in psychotic major depression, while the clinical outcomes tend to be similar in non-psychotic major depression in the short-term treatment. Future blinded randomised trials are required to compare the long-term clinical outcomes of both methods in clinically-homogeneous samples with major depression.